Intervención holística en los procesos de reducción de riesgos de los habitantes de la comunidad Gradas – cantón Guaranda 2021 - Arévalo Chochos, Carmen Mónica (2022)
The present case study was carried out looking at the problem in the community of Gradas on the holistic intervention of the inhabitants of the community of Gradas in the processes of risk reduction, which is essential to understand the nature and magnitude of the risks and the intervention of the inhabitants in them. In this way, the present case study seeks to investigate and analyze the intervention of the inhabitants of the Gradas community in the city of Guaranda in the face of the natural risks that they are exposed to, and it is also worth emphasizing the importance of providing the population with instruments, information and capacities, attitudes and practices that the population possesses to respond to an emergency. To meet the proposed objectives, a survey was applied to the inhabitants of the community of Gradas and the literature review of the PDOT, as well as to determine the level of intervention, the participation level matrix was used at the national and local levels, where The surveys were applied to a representative per family of the community of Gradas, obtaining the result of the same, a model of participation in the processes of risk reduction was proposed to serve as a guide for the elaboration of emergency and contingency plans against natural risks. This case study is constituted as follows: CHAPTER I, this chapter contains the statement of the problem, formulation of the problem, justification objectives and reflection questions CHAPTER II, the scientific foundation is included. 18 CHAPTER III, the methodological framework that was used for the investigation is exposed; level of research, population and sample, as well as the techniques and instruments for collecting information, processing techniques and analysis of results. CHAPTER IV, this chapter presents the results obtained according to the established objectives CHAPTER V, Contains the conclusions and recommendations It concludes with the bibliography and the ann